The mangrove with sediment's evolution and Paleoclimate in the Holocene at the Red river mouth - Thuận, Đinh Văn; Dỹ, Nguyễn Địch; Trí, Nguyễn Hoàng; Dương, Nguyễn Thùy (Vietnam Journal of Earth Sciences, 2018)
There are four successive